2015
DOI: 10.2139/ssrn.2664329
|View full text |Cite
|
Sign up to set email alerts
|

Competition between and within Universities: Theoretical and Experimental Investigation of Group Identity and the Desire to Win

Abstract: We study how salient group identity, created through competition between students from different universities, as well as differences in the value of winning impact competitive behavior. Our experiment employs a simple all-pay auction within and between two university subject pools. We find that when competing against their peers, students within the lower tier university bid more aggressively than students within the top-tier university. Also, students from the lower tier university, in particular women, bid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…2 Datta Gupta et al (2013) report that choosing the gender of a potential competitor influences competitiveness. Chen et al (2015) find that a salient group identity stiffens the competition between different universities. Chowdhury et al (2016) show that a more salient group identity (natural vs. minimal) escalates conflicts in a contest by motivating people to increase their effort.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…2 Datta Gupta et al (2013) report that choosing the gender of a potential competitor influences competitiveness. Chen et al (2015) find that a salient group identity stiffens the competition between different universities. Chowdhury et al (2016) show that a more salient group identity (natural vs. minimal) escalates conflicts in a contest by motivating people to increase their effort.…”
Section: Introductionmentioning
confidence: 84%
“…Studies of group identity and cooperation have shown the importance of in-group favoritism, i.e., people treat more generously someone who shares the same group identity than someone who belongs to another social group (e.g., Charness et al, 2007;Chen et al, 2009;Goette et al, 2012). 1 Much less research has been conducted on the importance of group identity in competitive settings (e.g., Datta Gupta et al, 2013;Chen et al, 2015;Chowdhury et al, 2016;Kato et al, 2016). 2 Our contribution to this literature is exploring the impact of group identity on unethical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2015) find that a salient group identity stiffens the competition between different universities. Chowdhury et al (2016) show that a more salient group identity (natural vs. minimal) escalates conflicts in a contest by motivating people to increase their effort.…”
Section: Introductionmentioning
confidence: 84%
“…1 Much less research has been conducted on the importance of group identity in competitive settings (e.g., Datta Gupta et al, 2013;Chen et al, 2015;Chowdhury et al, 2016;Kato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of group identity and cooperation have shown the importance of in-group favoritism, i.e., people treat more generously someone who shares the same group identity than someone who belongs to another social group (e.g., Charness et al, 2007;Chen et al, 2009;Goette et al, 2012). 1 Much less research has been conducted on the importance of group identity in competitive settings (e.g., Datta Gupta et al, 2013;Chen et al, 2015;Chowdhury et al, 2016;Kato et al, 2016). 2 Our contribution to this literature is exploring the impact of group identity on unethical behavior.…”
Section: Introductionmentioning
confidence: 99%